Cover Feature: The Nature of the Atypical Kinetic Effects Observed for the Thermally Induced Spin Transition in Ferrous Nitroprussides with Short Organic Pillars (Eur. J. Inorg. Chem. 24/2022). Issue 24 (27th July 2022) - Avila, Yosuan; Scanda, Karla; Díaz‐Paneque, Luis A.; Cruz‐Santiago, Lorenzo A.; González, Marlene; Reguera, Edilso
Abstract : The Cover Feature shows the effect of the repulsive electrostatic interaction in the interlayer region of 2D ferrous nitroprussides with short pillar molecules on the spin transition kinetics. Wider hysteresis loops were observed for the lower scan rates. This is an effect opposite to that expected under conditions close to those corresponding to the thermodynamic equilibrium. The axial CN ligand and the NO group found in the interlayer region accumulate electron density, via π‐back donation, in their N and O ends. These charge centers result in a repulsive electrostatic interaction between adjacent layers, which opposes the HS→LS transition during the cooling of the sample and favors the inverse (LS→HS) transition. Since the spin transition is closely related to the nucleation and growth of the new structural phase, the observed effect of the scan rate value on the width of the hysteresis loop was discussed in terms of structural changes. More information can be found in the Research Article by M. González, E. Reguera and co‐workers .